Iniciativas supranacionales ante la corrupción en el deporte y su incidencia en el ordenamiento jurídico español: el ejemplo del consejo de Europa - Sánchez Bernal, Javier (2019)
In the last years, sports have increased their economic dimension, being considered not only a healthy social practice. This fact has contributed for the appearance of a new criminality, based on fraud and corruption, linked to manipulation of sports competitions and sports bettings. Because of that, international concern for fighting against these behaviors has been strengthened. In this context, the Council of Europe, a supranational pioneering institution in sports area, approved the Convention on Manipulation of Sports Competitions in 2014. This text contains educational and awareness-raising policies, preventive and cooperative measures, and encourages each Party to criminalise several illicit acts in sports